Covenant and Community in Early Rabbinic Literature - Novick, Tzvi 1976- (2024)
This article concerns the role of covenant in early rabbinic literature in relation to biblical and especially Second Temple-era predecessors. The first part establishes that the Qumran sectarians and earlier circles were drawn to the concept of covenant because it represented, especially through the mechanism of covenant renewal, a powerful tool for defining and supporting group identity. The second part shows that for the rabbis, the importance of covenant lay chiefly, instead, in its capacity to conceptualize the notion of Israel as a collective body defined by corporate responsibility. The third part suggests that this novel deployment of covenant arose in part to counter the individuating force of halakah as law, another innovation of the rabbis.
Keywords: Deuteronomy 29; Qumran; Corporate Identity; Covenant; Halakah; Rabbinic Literature